Genomic screening in rare disorders: New mutations and phenotypes, highlighting ALG14 as a novel cause of severe intellectual disability. Issue 6 (15th October 2018) - Kvarnung, Malin; Taylan, Fulya; Nilsson, Daniel; Anderlid, Britt‐Marie; Malmgren, Helena; Lagerstedt‐Robinson, Kristina; Holmberg, Eva; Burstedt, Magnus; Nordenskjöld, Magnus; Nordgren, Ann; Lundberg, Elisabeth S.
Abstract : We have investigated 20 consanguineous families with multiple children affected by rare disorders. Detailed clinical examinations, exome sequencing of affected as well as unaffected family members and further validation of likely pathogenic variants were performed. In 16/20 families, we identified pathogenic variants in autosomal recessive disease genes ( ALMS1, PIGT, FLVCR2, TFG, CYP7B1, ALG14, EXOSC3, MEGF10, ASAH1, WDR62, ASPM, PNPO, ERCC5, KIAA1109, RIPK4, MAN1B1 ). A number of these genes have only rarely been reported previously and our findings thus confirm them as disease genes, further delineate the associated phenotypes and expand the mutation spectrum with reports of novel variants. We highlight the findings in two affected siblings with splice altering variants in ALG14 and propose a new clinical entity, which includes severe intellectual disability, epilepsy, behavioral problems and mild dysmorphic features, caused by biallelic variants in ALG14. Abstract :